Effect of Overexpression of the Brain-Specific Na+/Ca2+ Exchanger Splice Variant NCX1.5 on NO Cytotoxicity in HEK293 Cells - Yuki Ota; Takuya Kawanai; Ryo Watanabe; Akira Nishimura; Yukio Ago; Kazuhiro Takuma; Toshio Matsuda (Elsevier, 2013)
Abstract.: Nitric oxide (NO) induces cytotoxicity in neuronal and glial cells via activation of the Na+/Ca2+ exchanger (NCX). This study examined the role of the predominant brain-specific NCX splice variant NCX1.5 in NO-induced cytotoxicity in the HEK293 cell expression system. Cells were transfected with the plasmid construct pcDNA3.1/V5-His containing full-length rat NCX1.5 cDNA. There was no difference in the cytotoxic effects of the NO donors sodium nitroprusside and S-nitroso-N-acetylpenicillamine between control and transfected cells. These results suggest that NO cytotoxicity is not dependent on NCX1.5. Keywords:: Na+/Ca2+ exchanger, nitric oxide, cytotoxicity